Parafunctional habits among dental students in the city of Recife, state of Pernambuco, Brazil: A cross-sectional study (Research, Society and Development, 2025)
Objective: This study aimed to understand the association between parafunctional habits of dentistry students in the city of Recife and academic life. Methodology: An observational, cross-sectional study was carried out through a questionnaire answered by dentistry students who were regularly enrolled in public or private colleges in the city of Recife. Data was collected through a structured questionnaire on Google Forms® platform and included in a Microsoft Excel® database spreadsheet. Data analysis was performed using descriptive statistics to analyze the frequency of associations with Chi-Square tests and Fisher's Exact Test. Results: The sample consisted of 276 students with a mean age of 21.36 years, and it was observed that the majority were from private institutions. There was a statistically significant association between anatomical and physiological knowledge of the stomatognathic system and the abandonment of parafunctional habits (p